2022
DOI: 10.1002/ccd.30352
|View full text |Cite
|
Sign up to set email alerts
|

Minimalistic hybrid approach for the percutaneous treatment of chronic coronary total occlusions: An in‐depth analysis of the whole algorithm

Abstract: Introduction:The minimalistic hybrid approach (MHA) is an algorithm to perform chronic total occlusion (CTO) percutaneous coronary intervention (PCI). The current study aims to evaluate the distribution of patients among the five different treatment strategies, the different techniques used in each strategy, the overall procedural success, and the safety of the MHA algorithm.Methods: Data from a consecutive series of patients with a CTO who underwent elective PCI between February 2019 and July 2021 were prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Initial results are promising, out of 56 performed CTO PCIs in a prospective study, there was 94.6% and 91.1% technical and procedural success, respectively [84]. A similar success rate was seen in the analysis of 143 CTO PCIs [85]. There is still a need for further research, but newly developed devices have shown some promise.…”
Section: Crossing Techniquesmentioning
confidence: 75%
“…Initial results are promising, out of 56 performed CTO PCIs in a prospective study, there was 94.6% and 91.1% technical and procedural success, respectively [84]. A similar success rate was seen in the analysis of 143 CTO PCIs [85]. There is still a need for further research, but newly developed devices have shown some promise.…”
Section: Crossing Techniquesmentioning
confidence: 75%
“…We extrapolated data from the BWG‐CTO registry, dividing CTO procedures into two groups depending on the algorithm used. Specifically, CTO PCI procedures performed using the “classic” hybrid algorithm or other algorithms not contemplated in the hybrid (with more focus on advanced antegrade techniques) were considered in the Conventional group, whereas all CTO PCIs performed following the MHA 11 were performed in one center by three different operators (PA, BS, and CZ) and were considered in the Minimalistic group. Of note, operators in both groups were proficient with the most up‐to‐date CTO crossing algorithms, and performed an annual range of 40–100 CTO procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Of note, operators in both groups were proficient with the most up‐to‐date CTO crossing algorithms, and performed an annual range of 40–100 CTO procedures. The MHA algorithm has been extensively described elsewhere (see Supplemental Material and Figure for more detailed MHA description) 11,12 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation